HUBUNGAN PELECEHAN SEKSUAL DAN KONFLIK PERAN DENGAN DUKUNGAN SOSIAL SEBAGAI VARIABEL MODERASI - Nuraini, Dewi (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
The issue of sexual harassment had attention from the larger enterprises and the mass media of the 1980, because there is an increase in job or profession for women, especially in traditional work environments. One of the professions that are vulnerable to sexual harassment was a caddy female profession, which in this study as sample. The hypothesis proposed in this study were sexual harassment and social support had significant impact on role conflict and sexual harassment had significant impact on role conflict with social support as moderated variable. Testing the hypothesis in this study using simple, multiple and moderation regression to know social support as the independent variable or moderation variable. The result of this research showed that sexual harassment and social support had significant impact on role conflict. Beside that, sexual harassment had significant impact on role conflict with social support as moderated variable, so social support can act as an independent variable, as well as moderated variables.